Preparation method of dopamine-coated poly (L-lactic acid) piezoelectric biological material
By introducing dopamine as a heteronucleating agent in poly(L-lactic acid) piezoelectric biological materials, the interface anchoring effect is used to promote the self-polarization and crystal nucleation of poly(L-lactic acid), and poly(L-lactic acid) is solved by using the interface anchoring effect, poly(L-lactic acid) is solved ) The problem of weak and unstable piezoelectric properties has achieved significantly enhanced piezoelectric properties and stability.
Patent Information
- Application Number
- CN202411660446.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing piezoelectric biomaterials based on poly(L-lactic acid) have problems with weak piezoelectric properties and are difficult to achieve long-term high voltage piezoelectric properties.
Dopamine is used as a heteronucleating agent to promote the self-polarization of poly(L-lactic acid) and crystal nucleation through the interface anchoring effect to prepare dopamine-coated poly(L-lactic acid) piezoelectric biological materials.
Significantly enhances piezoelectric performance and stability, providing good protection for implantable and biodegradable biomedical piezoelectric devices.
Smart Images

Figure CN119392403A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of piezoelectric biomaterials, and in particular to a method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial. Background Art
[0002] Piezoelectric biomaterials are an important class of functional materials that can be used in state-of-the-art human-machine interfaces, energy conversion, and sensing technologies. In modern bioelectronic systems, functional nanofibers and their related nonwovens are particularly attractive for wearable and implantable devices that interface with soft tissues. Poly(L-lactic acid) is a piezoelectric biopolymer material widely used in medical implants. If the appropriate crystal phase, orientation, and morphology can be achieved, it provides a good platform for the development of implantable and biodegradable piezoelectric devices. However, the weak and unstable piezoelectricity of poly(L-lactic acid) remains a major challenge for its practical application. Although the crystallinity and orientation of poly(L-lactic acid) can be improved by thermal annealing and mechanical stretching, the piezoelectric poly(L-lactic acid) bulk films prepared by the stretching method usually have defects such as low β-phase ratio, poor stability, and high rigidity.
[0003] Electrospinning can effectively produce self-polarized soft piezoelectric poly(L-lactic acid) nanofibers with high crystallinity due to the high stretching force applied to the charged solution jet. However, the polarized poly(L-lactic acid) will partially rearrange under mechanical stretching or even temperature fluctuations of thermal motion, and thus tends to depolarize or relax back to the more thermodynamically stable non-piezoelectric phase. Achieving and maintaining high-voltage piezoelectric properties for a long time remains one of the biggest challenges in the development of flexible piezoelectric biomaterials based on poly(L-lactic acid). Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial in view of the problem that the piezoelectric biomaterial based on poly (L-lactic acid) prepared by the existing method has weak piezoelectricity and instability. The method uses dopamine as a heterogeneous nucleating agent to solve the long-standing stability problem of piezoelectric poly (L-lactic acid), providing a good guarantee for the development of implantable and degradable biomedical piezoelectric devices.
[0005] To achieve the above object, the present invention is implemented by the following technical solutions:
[0006] The present invention provides a method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial, the method comprising the following steps:
[0007] S1. Preparation of dopamine hydrochloride dispersion: ultrasonically dispersing dopamine hydrochloride in an organic solvent to obtain a dopamine hydrochloride dispersion;
[0008] S2, preparation of electrospinning solution: adding poly (L-lactic acid) powder to the dopamine hydrochloride dispersion and stirring to obtain an electrospinning solution;
[0009] S3. Preparation of dopamine-coated poly (L-lactic acid) piezoelectric biomaterial: remove the bubbles in the electrospinning solution, and then obtain a nanofiber membrane through an electrospinning process, and then anneal the nanofiber membrane at a high temperature and cool it to obtain a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial.
[0010] Specifically, the preparation method of the present invention adopts the interfacial anchoring effect, which is responsible for anchoring the self-polarized poly (L-lactic acid) chain and promoting crystal nucleation through the strong intermolecular interaction at the interface between dopamine and poly (L-lactic acid), so that the prepared piezoelectric biomaterial exhibits significantly enhanced piezoelectric properties and excellent service life.
[0011] Furthermore, a method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial is provided: Step S1, preparation of a dopamine hydrochloride dispersion: dissolving dopamine hydrochloride in an organic solvent and ultrasonically treating the dopamine hydrochloride dispersion to obtain a dopamine hydrochloride dispersion; wherein the concentration of the dopamine hydrochloride is 0.1 to 5.0 mg / ml.
[0012] Furthermore, a method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial: the organic solvent described in step S1 is hexafluoroisopropanol.
[0013] Furthermore, a method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial: the ultrasonic treatment time in step S1 is 30 to 60 minutes.
[0014] Furthermore, a method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial is provided: Step S2, preparation of an electrospinning solution: adding poly (L-lactic acid) powder to the dopamine hydrochloride dispersion and magnetically stirring at 40 to 50° C. at a speed of 300 to 500 rpm for 1 to 3 hours to obtain an electrospinning solution.
[0015] Furthermore, a method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial: in step S2, the concentration of the spinning raw material poly (L-lactic acid) powder in the electrospinning solution is 0.05-0.2 g / ml.
[0016] Furthermore, a method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial is provided: Step S3, preparation of dopamine-coated poly (L-lactic acid) piezoelectric biomaterial: the electrospinning solution is allowed to stand for 1 to 3 hours to remove bubbles therein, and then a nanofiber membrane is obtained by an electrospinning process, and then the nanofiber membrane is annealed at 100 to 110° C. for 3 to 10 hours, and then cooled to room temperature, thereby obtaining a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial.
[0017] Preferably, the annealing temperature is 105° C. and the annealing time is 10 hours.
[0018] Furthermore, a method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial is provided: the electrospinning process parameters in step S3 are: spinning temperature of 21-25°C, humidity of 35-45%, voltage of 10-20 kV, propulsion speed of 0.5-2.0 ml / h, receiving distance of 5-15 cm, and the needle is a No. 21 flat-mouth needle.
[0019] Preferably, the electrospinning process parameters are: spinning temperature of 23° C., humidity of 40%, voltage of 15 kV, propulsion speed of 0.5 to 2.0 ml / h, receiving distance of 5 to 15 cm, and a No. 21 flat needle.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention adopts an interface anchoring strategy to solve the long-standing stability problem in piezoelectric poly (L-lactic acid) nanofibers by introducing dopamine as a heterogeneous nucleating agent, and the self-assembly of dopamine into a shell layer is crucial for the formation and arrangement of β-phase poly (L-lactic acid), wherein the strong intermolecular interaction at the interface between dopamine and poly (L-lactic acid) is responsible for anchoring the self-polarized poly (L-lactic acid) chain and promoting crystal nucleation. The dopamine-coated poly (L-lactic acid) piezoelectric biomaterial prepared by the present invention is a core / shell structured nanofiber material that can exhibit significantly enhanced piezoelectric properties and excellent stability.
[0022] (2) The present invention proposes a practical strategy to solve the long-standing stability problem in the manufacture of piezoelectric poly (L-lactic acid) nanostructures, and opens up a new way to develop flexible and biodegradable electromechanical coupling devices for biomedical applications. The present invention uses an electrospinning process to achieve the preparation of dopamine-coated poly (L-lactic acid) piezoelectric biomaterials, and the process operation is simple and reproducible. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 This is a scanning electron microscope (SEM) image of the dopamine-coated poly (L-lactic acid) piezoelectric biomaterial obtained in Example 1 of the present invention;
[0025] Figure 2 This is a transmission electron microscope (TEM) image of the dopamine-coated poly (L-lactic acid) piezoelectric biomaterial obtained in Example 1 of the present invention;
[0026] Figure 3 This is a transmission electron microscope (TEM) image of the dopamine-coated poly (L-lactic acid) piezoelectric biomaterial obtained in Comparative Example 1 of the present invention;
[0027] Figure 4 XRD spectra of the dopamine-coated poly (L-lactic acid) piezoelectric biomaterial obtained in Example 1 of the present invention and the pure poly (L-lactic acid) fiber obtained in Comparative Example 1;
[0028] Figure 5 This is a diagram of the open circuit voltage of the piezoelectric materials obtained in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] Provided is a method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial, the method comprising the following steps:
[0032] S1. Preparation of dopamine hydrochloride dispersion: 5.0 ml of hexafluoroisopropanol was measured and added into a screw-mouth glass bottle, and then 5.0 mg of dopamine hydrochloride was added into the screw-mouth glass bottle. The screw-mouth glass bottle was tightened and sealed with a sealing film, and ultrasonically oscillated for 30 minutes to obtain a dopamine hydrochloride dispersion;
[0033] S2. Preparation of electrospinning solution: 0.5 g of poly (L-lactic acid) powder was weighed and added to the above-mentioned dopamine hydrochloride dispersion and magnetically heated and stirred at 40° C. and 400 rpm for 3 hours to obtain an electrospinning solution;
[0034] S3. Preparation of dopamine-coated poly (L-lactic acid) piezoelectric biomaterial: the obtained electrospinning solution was allowed to stand for 1 hour to remove bubbles therein, and then a nanofiber membrane was obtained by an electrospinning process, and then the nanofiber membrane was annealed at 105° C. for 10 hours, and then cooled to room temperature, thereby obtaining a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial;
[0035] The electrospinning process parameters are as follows: the spinneret is a No. 21 flat needle, the voltage is 15 kV, the receiving distance is 10 cm, the electrospinning is performed at a propulsion speed of 0.8 ml / h, the spinning temperature is 23° C., and the humidity is 40%.
[0036] The scanning electron microscope (SEM) image of the dopamine-coated poly (L-lactic acid) piezoelectric biomaterial obtained in Example 1 is as follows: Figure 1 As shown by Figure 1 It can be seen that dopamine uniformly wraps the poly (L-lactic acid) fibers and is widely present.
[0037] Example 2
[0038] Provided is a method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial, the method comprising the following steps:
[0039] S1. Preparation of dopamine hydrochloride dispersion: 5.0 ml of hexafluoroisopropanol was measured and added into a screw-mouth glass bottle, and then 0.5 mg of dopamine hydrochloride was added into the screw-mouth glass bottle. The screw-mouth glass bottle was tightened and sealed with a sealing film, and ultrasonically oscillated for 60 minutes to obtain a dopamine hydrochloride dispersion;
[0040] S2. Preparation of electrospinning solution: 0.25 g of poly (L-lactic acid) powder was weighed and added to the above-mentioned dopamine hydrochloride dispersion and magnetically heated and stirred at 45° C. and 300 rpm for 3 hours to obtain an electrospinning solution;
[0041] S3. Preparation of dopamine-coated poly (L-lactic acid) piezoelectric biomaterial: the obtained electrospinning solution was allowed to stand for 1 hour to remove bubbles therein, and then a nanofiber membrane was obtained by an electrospinning process, and then the nanofiber membrane was annealed at 100° C. for 6 hours, and then cooled to room temperature, thereby obtaining a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial;
[0042] The electrospinning process parameters are as follows: the spinneret is a No. 21 flat needle, the voltage is 10 kV, the receiving distance is 5 cm, the electrospinning is performed at a propulsion speed of 0.5 ml / h, the spinning temperature is 21° C., and the humidity is 35%.
[0043] Example 3
[0044] Provided is a method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial, the method comprising the following steps:
[0045] S1. Preparation of dopamine hydrochloride dispersion: 5.0 ml of hexafluoroisopropanol was measured and added into a screw-mouth glass bottle, and then 25.0 mg of dopamine hydrochloride was added into the screw-mouth glass bottle. The screw-mouth glass bottle was tightened and sealed with a sealing film, and ultrasonically oscillated for 45 minutes to obtain a dopamine hydrochloride dispersion;
[0046] S2. Preparation of electrospinning solution: 0.8 g of poly (L-lactic acid) powder was weighed and added to the above-mentioned dopamine hydrochloride dispersion and magnetically heated and stirred at 50° C. and 500 rpm for 2 hours to obtain an electrospinning solution;
[0047] S3. Preparation of dopamine-coated poly (L-lactic acid) piezoelectric biomaterial: the obtained electrospinning solution was allowed to stand for 2 hours to remove bubbles therein, and then a nanofiber membrane was obtained by an electrospinning process, and then the nanofiber membrane was annealed at 110° C. for 3 hours, and then cooled to room temperature, thereby obtaining a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial;
[0048] The electrospinning process parameters are as follows: the spinneret is a No. 21 flat needle, the voltage is 20 kV, the receiving distance is 15 cm, the electrospinning is performed at a propulsion speed of 2.0 ml / h, the spinning temperature is 25° C., and the humidity is 45%.
[0049] Comparative Example 1
[0050] The difference between Comparative Example 1 and Example 1 is that dopamine hydrochloride is not added in the process of preparing the piezoelectric material in Comparative Example 1, and the rest is the same as Example 1. Comparative Example 1 prepares pure poly (L-lactic acid) piezoelectric fiber material.
[0051] test:
[0052] (1) TEM data of the dopamine-coated poly (L-lactic acid) piezoelectric biomaterial obtained in Example 1 and the pure poly (L-lactic acid) piezoelectric fiber material obtained in Comparative Example 1 are shown in the figure below. Figure 2 He Ru Figure 3 As shown by Figure 2 and Figure 3It can be seen that compared with Example 1, the pure poly (L-lactic acid) piezoelectric fiber in Comparative Example 1 has no shell structure, that is, no dopamine shell.
[0053] (2) The XRD data of the dopamine-coated poly (L-lactic acid) piezoelectric biomaterial obtained in Example 1 and the pure poly (L-lactic acid) piezoelectric fiber material obtained in Comparative Example 1 were tested. The test results are as follows: Figure 4 As shown by Figure 4 It can be seen that the piezoelectric crystalline phase of the dopamine-coated poly (L-lactic acid) piezoelectric biomaterial is higher, which means stronger piezoelectric performance.
[0054] (3) Using a cutting device, the dopamine-coated poly (L-lactic acid) piezoelectric fiber material obtained in the above Example 1 and the pure poly (L-lactic acid) piezoelectric fiber material obtained in Comparative Example 1 are cut into pieces of 1 cm × 2 cm in size. Aluminum thin paper is used as the electrode for the upper and lower electrodes, and an insulating elastic material is used as a sealing protective layer to extend the cycle life. A sliding table device with a fixed frequency of 4 Hz is used to perform reciprocating stretching and squeezing motion. Finally, an electrometer is used to collect the output signal of the open circuit voltage of the nanogenerator. The output open circuit voltage is as follows: Figure 5 As shown by Figure 5 It can be seen that the dopamine-coated poly (L-lactic acid) piezoelectric biomaterial has a higher piezoelectric output.
[0055] The above are preferred embodiments of the present invention and are only used to explain the present invention, not to limit the present invention. Any obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial, characterized in that: The method comprises the following steps: S1. Preparation of dopamine hydrochloride dispersion: ultrasonically dispersing dopamine hydrochloride in an organic solvent to obtain a dopamine hydrochloride dispersion; S2, preparation of electrospinning solution: adding poly (L-lactic acid) powder to the dopamine hydrochloride dispersion and stirring to obtain an electrospinning solution; S3. Preparation of dopamine-coated poly (L-lactic acid) piezoelectric biomaterial: remove the bubbles in the electrospinning solution, and then obtain a nanofiber membrane through an electrospinning process, and then anneal the nanofiber membrane at a high temperature and cool it to obtain a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial.
2. The method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial according to claim 1, characterized in that: Step S1, preparation of dopamine hydrochloride dispersion: dissolving dopamine hydrochloride in an organic solvent and subjecting it to ultrasonic treatment to obtain a dopamine hydrochloride dispersion; wherein the concentration of the dopamine hydrochloride is 0.1 to 5.0 mg / ml.
3. The method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial according to claim 1 or 2, characterized in that: The organic solvent described in step S1 is hexafluoroisopropanol.
4. The method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial according to claim 1 or 2, characterized in that: The ultrasonic treatment time in step S1 is 30 to 60 minutes.
5. The method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial according to claim 1, characterized in that: Step S2, preparation of electrospinning solution: adding poly (L-lactic acid) powder to the dopamine hydrochloride dispersion and magnetically stirring at 40-50° C. at a speed of 300-500 rpm for 1-3 hours to obtain electrospinning solution.
6. The method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial according to claim 1 or 5, characterized in that: The concentration of the spinning raw material poly (L-lactic acid) powder in step S2 is 0.05 to 0.2 g / ml.
7. The method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial according to claim 1, characterized in that: Step S3, preparation of dopamine-coated poly (L-lactic acid) piezoelectric biomaterial: the electrospinning solution is allowed to stand for 1 to 3 hours to remove bubbles therein, and then a nanofiber membrane is obtained by an electrospinning process, and then the nanofiber membrane is annealed at 100 to 110° C. for 3 to 10 hours, and then cooled to room temperature to obtain a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial.
8. The method for preparing a dopamine-coated poly (L-lactic acid) piezoelectric biomaterial according to claim 1 or 7, characterized in that: The electrospinning process parameters in step S3 are as follows: spinning temperature is 21-25° C., humidity is 35-45%, voltage is 10-20 kV, propulsion speed is 0.5-2.0 ml / h, receiving distance is 5-15 cm, and the needle is a No. 21 flat needle.
Citation Information
Patent Citations
Application of poly-L-lactic acid fiber material in piezoelectric devices
CN107293639A
Lactic acid-based filter material, filter membrane, filter device and preparation method of filter material
CN108201735A
Bionic piezoelectric bracket for promoting bone repair as well as preparation method and application of bionic piezoelectric bracket
CN117224737A
Electrostatic spinning process for preparing poly-L-lactic acid / asparagine piezoelectric composite film
CN117721595A
Nanofiber web piezoelectric material obtained by electrospinning polylactic acid, method of producing same, piezoelectric sensor comprising same, and method of manufacturing the piezoelectric sensor
US20160190427A1